2021
DOI: 10.4103/eus-d-21-00118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biliary stents on the diagnostic accuracy of EUS-guided fine-needle biopsy of solid pancreatic head lesions: A multicenter study

Abstract: Background and Objectives: There is no clear evidence of a negative impact of biliary stents on the diagnostic yield of EUS-guided fine-needle biopsy (EUS-FNB) for diagnosing pancreatic head lesions. We aimed to evaluate the association between the presence of biliary stents and the diagnostic accuracy of EUS-FNB. Materials and Methods: A multicenter retrospective study including all jaundiced patients secondary to pancreatic head masses was performed. Patients were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…From 91 studies identified using the search strategy, we included seven retrospective case-control studies [ 10 , 11 , 12 , 13 , 18 , 19 , 20 ] ( Figure 1 ) with 2458 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From 91 studies identified using the search strategy, we included seven retrospective case-control studies [ 10 , 11 , 12 , 13 , 18 , 19 , 20 ] ( Figure 1 ) with 2458 patients.…”
Section: Resultsmentioning
confidence: 99%
“…There is conflicting evidence regarding the impact of biliary stents on the diagnostic accuracy of EUS-TA. This is likely due to poor visualization of the lesion from acoustic shadowing, reverberation and/or surrounding inflammation associated with the stent [ 9 , 10 , 11 ]. Additionally, these studies seem to suggest that plastic or self-expandable metal stents (SEMSs) could have a dissimilar effect because of differences in their material and diameter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biliary stents can lower the diagnostic accuracy of EUS-FNA from 95 to 65% in distal lesions, and from 86 to 56% in perihilar lesions because the access of the needle beyond the stent is restricted [ 76 ]. For this reason, it is recommended to remove the stent prior to EUS tissue acquisition, similar to pancreatic pathology, in which the diagnostic value of EUS-FNB is diminished by the presence of a biliary stent, regardless of its type [ 82 ]. Moreover, in the case of primary sclerosing cholangitis, the presence of multiple biliary stenosis and benign lymphadenopathy may make EUS-FNA more difficult [ 56 , 76 ].…”
Section: Eus Tissue Acquisition Of Mass-forming Cholangiocarcinomamentioning
confidence: 99%